2004
DOI: 10.1007/s00127-004-0697-9
|View full text |Cite
|
Sign up to set email alerts
|

Perception of stigma among patients with schizophrenia

Abstract: The relation between perception of stigmatization and symptoms is a vicious circle in which the elements reinforce each other. Interruption of this circle will increase the adaptive abilities and decrease the disability of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
3
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 15 publications
5
52
3
5
Order By: Relevance
“…[22] tarafından yapılan çalışmada örneklemin %52'sinde daha önce bir psikiyatrik yatış bulunmaktadır. Ertugrul ve Uluğ [25] tarafından yapılan çalışmada, psikiyatrik semptom puanı yüksek olanlarda ve yeti yitimi daha fazla olan hastalarda damgalanma puanları daha yüksek bulunmuş ayrıca, hezeyan, duygusal ve sosyal geri çekilme gibi semptomlar arttıkça damgalanma puanının da anlamlı düzeyde arttığı yönünde bulgular elde edilmiştir. Psikiyatrik tedavide, ayaktan tedavi uygulamaları öncelikle tercih edilmekle birlikte, tedavi programına uyum sağlama zorluğu, psikotik atak, çevreye zarar verme, eksitasyon, dezorganize davranış gösterme, intihar girişimi, günlük işlevselliğin ileri düzeyde bozulması gibi durumlarda hastaların yatırılarak tedavi edilmesi seçeneği tercih edilmektedir.…”
Section: Discussionunclassified
“…[22] tarafından yapılan çalışmada örneklemin %52'sinde daha önce bir psikiyatrik yatış bulunmaktadır. Ertugrul ve Uluğ [25] tarafından yapılan çalışmada, psikiyatrik semptom puanı yüksek olanlarda ve yeti yitimi daha fazla olan hastalarda damgalanma puanları daha yüksek bulunmuş ayrıca, hezeyan, duygusal ve sosyal geri çekilme gibi semptomlar arttıkça damgalanma puanının da anlamlı düzeyde arttığı yönünde bulgular elde edilmiştir. Psikiyatrik tedavide, ayaktan tedavi uygulamaları öncelikle tercih edilmekle birlikte, tedavi programına uyum sağlama zorluğu, psikotik atak, çevreye zarar verme, eksitasyon, dezorganize davranış gösterme, intihar girişimi, günlük işlevselliğin ileri düzeyde bozulması gibi durumlarda hastaların yatırılarak tedavi edilmesi seçeneği tercih edilmektedir.…”
Section: Discussionunclassified
“…The WHODAS II is designed for use in cross-national evaluations. To our knowledge, no studies have been published with the WHODAS II in Morocco, and only one study in Turkey [18].…”
Section: Assessmentsmentioning
confidence: 99%
“…Lysaker et al (2012) [11] assessed the stigma of people with schizophrenia who worked in a vocational rehabilitation program, finding that a decrease in self-stigma correlated with an increase in self-esteem. Several studies have demonstrated that more stigmatized people presented more symptoms [12][13][14]. Muñoz et al (2011) [15] found that psychosocial outcomes, especially those related to personal autonomy, were associated with social stigma in a group of people with mental illness.…”
Section: Relation Between Self-stigma and Social Functioningmentioning
confidence: 97%